Distribution and composition characteristics of microplastics in the coastal surface seawaters of Zhejiang Province - ZHOU Xiaotian; ZHAO Wenlu; LI Tiejun; WU Wei; GUO Yuanming; YANG Chenghu (浙江大学学报. 农业与生命科学版)
The surface seawater from 20 stations in the coastal waters (e.g. coastal sea areas of Pinghu, Daishan, Sanmen, Rui’an and Cangnan) of Zhejiang Province were collected from September to October in 2019. The abundance, chemical composition, shape and color of microplastics in the surface seawater were analyzed. The results indicated that the microplastics were widely distributed in the coastal surface seawaters of Zhejiang Province, and the average abundance of microplastics in various coastal areas were heterogeneous. The highest abundance of microplastics were recorded at Sanmen coastal area (240 piece/m3), and the Rui’an coastal area had the lowest microplastic abundance (70 piece/m3). The abundance of microplastics in the surface seawaters of all sampling stations ranged from 40 to 320 piece/m3, and the average abundance was 144 piece/m3. The most major chemical compositions of microplastics were polyester (38.9%) and cellulose (30.6%). Fiber, fragment and film were detected as the mainly shapes of microplastics, accounting for 86.1%, 12.5% and 1.4%, respectively. The most common colors were gray, blue and white, accounting for 25.0%, 23.6% and 19.4%, respectively. The characteristic analysis showed that the microplastics in the coastal surface seawaters of Zhejiang Province mainly originated from textile industry, fishery and domestic sewage. The microplastic was unevenly distributed in the nearshore water resulting from the effects of wind power, ocean current, runoff and seawater dilution. Compared with other domestic studies using the similar methods, the abundance of microplastics in the surface seawater of Zhejiang coastal area was at a relatively low level. This study can provide valuable data for the migration and pollution risk assessment of microplastics in coastal waters of Zhejiang Province.